MEKANISME PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL MELALUI DISPUTE SETTLEMENT BODY (DSB) WORLD TRADE ORGANIZATION (WTO) (TINJAUAN TERHADAP GUGATAN INDONESIA KEPADA KOREA SELATAN DALAM PENGENAAN BEA MASUK ANTI-DUMPING PRODUK KERTAS) - Diah Ratnasari; Ida Ayu Sukihana (Kertha Negara : Journal Ilmu Hukum, 2014)
This writing shall be entitled as “Mechanism of Trade Dispute Settlementthrough World Trade Organization (WTO) Dispute Settlement Body (DSB) (Analysistowards Indonesia vs South Korea on Income Tarrif of Anti-dumping for Paper-relatedProduct Case)”. This writing shall apply normative legal research method combinedwith several approaches of regulatory, casuistic, and factual approach respectively.This writing shall illustrate the chronological order of dispute settlement sequences ofthe related case between Indonesia and South Korea. Conclusion drawn from thiswriting shall be illustrating the mechanism initiated by bilateral consultation whichshall be proceeded with the establishment of WTO DSB Panel which furtherrecommended that the South Korea to conduct a review regarding Anti-DumpingAgreement (ADA) provision of Indonesian paper-related product.